The effect of FDI Net Inflow on the GDP growth rate: 1990-2021 - Chike, Nwosu Kanayo; Oguanobi, Chimezie Alex; Mbamalu, Euphemia Ifunanya; Egbunike, Chinedu Francis (Goodwood Publishing, 2023)
Purpose: This study investigates the impact of foreign direct investment (FDI) net inflows on Nigeria’s gross domestic product (GDP) growth rate from 1990 to 2021, addressing the ongoing debate on the role of FDI in fostering sustainable economic growth. Methods: The research employed an ex post facto design using secondary data obtained from the World Bank’s World Development Indicators. Stationarity was tested using the Augmented Dickey-Fuller (ADF) unit root test. Ordinary Least Squares (OLS) regression was applied, complemented by robustness checks using Dynamic Ordinary Least Squares (DOLS), to test the hypotheses and validate the model. Results: Findings reveal that FDI net inflows significantly and positively affect GDP growth in Nigeria (p<0.05). Control variables such as the degree of economic openness (DEGO) and inflation (INFL) showed positive but statistically non-significant effects under OLS, though DOLS results indicate DEGO as positive and significant while INFL was negative and significant. The results confirm that FDI contributes to economic growth by promoting capital accumulation, technology transfer, and managerial expertise. Conclusion: The study concludes that FDI net inflows play a critical role in driving Nigeria’s economic growth. Policies aimed at improving openness, institutional quality, and macroeconomic stability are necessary to maximize the benefits of FDI. Limitations: The analysis is limited to Nigeria’s data and selected control variables, restricting broader generalization across Sub-Saharan Africa. Contribution: This study enriches the literature on FDI-growth nexus in developing economies, offering policy insights for enhancing sustainable growth through effective FDI management.